Nondestructive Evaluation of Non-Strand Defects in Stay Cable Specimens. Issue 41 (December 2018) - Karthik, Madhu M.; Terzioglu, Tevfik; Jones, Casey; Hurlebaus, Stefan; D. Hueste, Mary Beth
Stay cable systems are used extensively for the construction of long-span bridges owing to their inherent advantages. In most cable-stayed bridges the steel strands within the main tension elements (MTEs) are grouted to provide a corrosion protection system. However, there could be segregated grout, voids, and water accumulation/infiltration within these voids in the ducts due to poor quality of the grouting material and grouting techniques. These locations may act as initiators for the corrosion of steel strands within the ducts, which can have serious implications on the load carrying capacity and safety of cable-stayed bridges. In this investigation, several nondestructive evaluation (NDE) techniques are evaluated to determine their ability to detect grout defects within the anchorage regions, end caps, and MTEs of the stay cable system. Four stay cable specimen mock-ups with known grout defects and voids were fabricated. NDE methods that were part of this investigation included ground penetrating radar, infrared thermography, electrical capacitance tomography, impact echo, sounding, ultrasonic tomography, ultrasonic pulse velocity, low frequency ultrasound, visual testing, and borescope. While a few NDE methods could identify voids and water infiltration defects within the high-density polyethylene (HDPE) MTEs, it is evident that there is still a need for a method that is effective in detecting grout defects within the metal ducts embedded in the anchorage region and metal MTEs. Although visual testing and borescope methods are effective in identifying the defects, prior information about the location of the defects is generally required.